2010
DOI: 10.1002/da.20744
|View full text |Cite
|
Sign up to set email alerts
|

Trauma-focused cognitive behavioral therapy for children: impact of the trauma narrative and treatment length

Abstract: TF-CBT, regardless of the number of sessions or the inclusion of a TN component, was effective in improving participant symptomatology as well as parenting skills and the children's personal safety skills. The eight session condition that included the TN component seemed to be the most effective and efficient means of ameliorating parents' abuse-specific distress as well as children's abuse-related fear and general anxiety. On the other hand, parents assigned to the 16 session, no narrative condition reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
241
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 336 publications
(253 citation statements)
references
References 21 publications
5
241
0
7
Order By: Relevance
“…O número de sessões de exposição à memória traumática é uma importante variável que vem sendo estudada com o intuito de verifi car sua possível relação com os resultados de intervenções cognitivo-comportamentais. Em estudo recente, crianças e adolescentes que receberam tratamento com 16 sessões apresentaram menos sintomas de reexperiência da memória traumática e evitação, quando comparados aqueles que receberam tratamento com oito sessões (Deblinger et al, 2011). Na avaliação do modelo de grupoterapia para meninas vítimas de VS (Habigzang et al, 2009) houve redução signifi cativa na quantidade de sintomas de TEPT nas três categorias avaliadas -revivência, evitação e hipervigilância.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…O número de sessões de exposição à memória traumática é uma importante variável que vem sendo estudada com o intuito de verifi car sua possível relação com os resultados de intervenções cognitivo-comportamentais. Em estudo recente, crianças e adolescentes que receberam tratamento com 16 sessões apresentaram menos sintomas de reexperiência da memória traumática e evitação, quando comparados aqueles que receberam tratamento com oito sessões (Deblinger et al, 2011). Na avaliação do modelo de grupoterapia para meninas vítimas de VS (Habigzang et al, 2009) houve redução signifi cativa na quantidade de sintomas de TEPT nas três categorias avaliadas -revivência, evitação e hipervigilância.…”
Section: Discussionunclassified
“…A Terapia Cognitivo-Comportamental (TCC) vem sendo utilizada com crianças e adolescentes vítimas de VS e obtendo evidências de efetividade em estudos internacionais (Deblinger, Mannarino, Cohen, Runyon, & Steer, 2011;Hetzel-Riggin, Brausch, & Montgomery, 2007) e nacionais (Habigzang et al, 2009;Lucânia, Valério, Barison, & Miyazaki, 2009). Os estudos nacionais, no entanto, foram realizados apenas com meninas.…”
unclassified
“…These investigations have involved a range of traumas, including sexual abuse (Deblinger, Mannarino, Cohen, Runyon, & Steer, 2011), domestic and community violence, natural and man-made disasters, neglect, and traumatic grief (CATS consortium, 2010; Kameoka et al, 2015; Lyons, Weiner, & Scheider, 2006; Murray et al, 2015; Salloum et al, 2016). …”
Section: Brief Review Of Empirical Support For Tf-cbtmentioning
confidence: 99%
“…Cognitive behavioral methods have also demonstrated to be significantly effective in demonstrating positive outcomes with child sexual abuse victims in children [25], and in adult survivors [8,26]. Cognitive-behavioral therapy (CBT) methods stem from the central principle that an individual's cognitions play a significant and primary role in the development and maintenance of emotional and behavioral responses to life situations.…”
Section: Treatment For Trauma Associated With Child Sexual Abusementioning
confidence: 99%
“…Children who have undergone this treatment have demonstrated significantly more improvement in PTSD, depression, and other emotional and behavioral symptoms after TF-CBT than after child-centered therapy [30]. Empirical evidence has shown that reviews completed regarding sexual abuse treatment literature documented TF-CBT as having very high empirical support for its effectiveness [25,26,30,32]. Trauma-Focused Cognitive Behavioral Therapy (TF-CBT) is believed to truly address and be the most effective with victims of trauma [33].…”
Section: Trauma-focused Cognitive Behavioral Therapymentioning
confidence: 99%